Beyond Clinical Boundaries: Medical Workers as Essential Partners in Addressing Social Determinants of Health Within Integrated Care Ecosystems (The Review of Diabetic Studies, 2024)
Healthcare systems increasingly recognize that addressing social determinants of health (SDOH) is essential for improving population health outcomes and reducing disparities. This study examines the evolving role of medical workers as key partners in identifying and addressing SDOH within integrated care ecosystems. Drawing on current research and implementation experiences, we explore how healthcare professionals across disciplines are expanding beyond traditional clinical boundaries to address the social factors that profoundly influence health. The Accountable Health Communities Screening Tool and similar instruments have standardized SDOH assessment in clinical settings, while various implementation patterns of integrated behavioral health demonstrate how practices incorporate SDOH into their workflows. Despite promising developments in screening tools, team-based approaches, and community partnerships, significant challenges remain, including workflow integration, sustainable financing, and ethical considerations in SDOH screening. We analyze how alternative payment models, policy developments, and workforce initiatives can support medical workers in addressing SDOH more effectively. The study concludes by outlining future directions for building sustainable ecosystems that support SDOH integration, including advancing technological solutions, strengthening multi-sector collaboratives, centering health equity, and enhancing interprofessional education. By embracing expanded roles in addressing social needs, medical workers can contribute to more effective, equitable healthcare systems that improve outcomes for individuals and communities, particularly those experiencing social vulnerability.